Evaluation and influencing factors of farmers’ sustainable livelihood response to ecocultural tourism in minority areas of China - Wu, Jilin; Zuo, Jinyou; Li, Li; Liu, Shuiliang (Frontiers in Environmental Science, 2023)
Ecocultural tourism is of great significance for regional poverty reduction and sustainable development of farmers' livelihoods. Obtain the data of 327 households from six ecocultural tourism villages in minority area of China. Principle component analysis and multiple linear regression were used to analyze the types and levels of response of the farmers to ecocultural tourism and determine the factors influencing this response. The study results revealed the following: (1) The responses of farmers’ regarding their sustainable livelihood could be divided into six types, which had an unbalanced distribution. (2) The overall levels of response of the farmers increased in the following order: complete response, balanced development, cultural network, ecology-dominant, developmental delay, and resource advantage response types. The overall response values were low. (3) The response characteristics for differing sustainable livelihood factors varied. Response was strong only for cultural and ecological capital factors. Response was relatively weak for material, natural, social, financial, and workforce capital factors. (4) There are five influencing factors of farmers' sustainable livelihood response and the influencing degree from high to low is the number of family members participating in tourism, rural tourism investment, the number of relatives and friends, family members participating in social affairs and the degree of national building protection. Strategies and suggestions for livelihood transformation, livelihood strategy selection, and livelihood improvement were proposed.